2017
DOI: 10.1111/ejss.12436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding biochar on the properties and nitrogen bioavailability of an acidic soil

Abstract: Biochar has attracted global attention because of its widespread application to improve soil quality and enhance soil productivity. Five types of biochar were prepared from peanut shells at 200–600°C by slow pyrolysis, and their physicochemical properties were investigated. Biochar was produced at 300 and 400°C, PBC300 and PBC400, respectively. The two forms of biochar were evaluated as soil amendments with an incubation and a pot experiment in a soil that had become acidified because of excessive use of nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Our previous work has shown that high VM content in macadamia nutshell biochar strongly reduced nitrogen availability in soil [13]. Other researchers have also observed the immobilization of N in soils receiving low-temperature [11,[60][61][62] and high VM biochars [12], in addition to increases in nitrous oxide and carbon dioxide emissions [63] and reductions in plant N concentrations [64]. Nitrogen immobilization can also increase in soils amended with both crop residues and biochar [65], with biochar inducing the preferential utilization of litter by microbes [66].…”
Section: Discussionmentioning
confidence: 90%
“…Our previous work has shown that high VM content in macadamia nutshell biochar strongly reduced nitrogen availability in soil [13]. Other researchers have also observed the immobilization of N in soils receiving low-temperature [11,[60][61][62] and high VM biochars [12], in addition to increases in nitrous oxide and carbon dioxide emissions [63] and reductions in plant N concentrations [64]. Nitrogen immobilization can also increase in soils amended with both crop residues and biochar [65], with biochar inducing the preferential utilization of litter by microbes [66].…”
Section: Discussionmentioning
confidence: 90%
“…Biochar addition decreased soil compaction and led to an increase in the proliferation of fine roots (increasing specific root length and reducing root tissue density) and promoted crop development (Olmo et al, ). Warmer soil temperatures and optimal soil bulk density could improve the growth of winter wheat (Liu et al, ), whereas soil with a bulk density that is too low might inhibit plant growth by affecting the availability of nutrients and water (Mandal et al, ; Wang et al, ). Therefore, further research is needed to establish the relations between root properties and changes in soil properties affected by biochar.…”
Section: Discussionmentioning
confidence: 99%
“…Cation exchange capacity is strongly pH-dependent on tropical soils and some alkaline biochars can raise the soil pH and, consequently, the soil CEC [32,56,71], with a concomitant contribution of the biochar CEC itself [35]. In a soil acidified by the excessive use of N fertilizers, the use of peanut shell-derived biochar (300-400 • C) increased the pH, CEC, SOM, as well as the maize biomass by 15-33% [72].…”
Section: Modelling the Effects Of Biochar On Soil Cecmentioning
confidence: 99%